Association between Perceived Health-Related Quality of Life and Depression with Frailty in the FRASNET Study - Delli Zotti, Giulia B.; Citterio, Lorena; Farinone, Sara; Concas, Maria Pina; Brioni, Elena; Zagato, Laura; Messaggio, Elisabetta; Faienza, Sipontina; Simonini, Marco; Napoli, Alessandra; Di Mattei, Valentina; Rovere-Querini, Patrizia; et al. (International journal of environmental research and public health, 2022)
Frailty is a major challenge facing the aging world. The phenotype of the frail subject is still far from being satisfactorily defined. We report data on mood, cognition, and quality of life (QoL) in relation to anamnestic factors, health, and socio-economic status in the FRASNET geriatric population (1204 subjects in stable health conditions), which is an observational cohort study that includes fairly balanced groups of Italian frail (421, 35%), pre-frail (449, 37.3%) and robust (334, 27.7%) subjects. A conditional inference tree analysis revealed a substantial influence of psychological variables on frailty. The physical indicator of QoL (Short Form Survey-36-Physical Component Summary, SF-36-PCS) was the predominant variable in the full model (threshold at 39.9, p < 0.001): higher frailty was found in subjects with a caregiver and lower SF-36-PCS. Frailty was also associated with the mental indicator of QoL (Short Form Survey-36-Mental Component Summary, SF-36-MCS), depression (Geriatric Depression Scale, GDS-15), leisure activities, and level of education. In support of the prominent role of inflammation in aging and mental illness, the SF-36-PCS score was correlated with the blood concentration of C-X-C motif chemokine ligand 10 (CXCL10) (r Pearson −0.355, p = 0.015), a critical signal in cell senescence and inflammaging, while the rs7567647 variant in FN1 gene encoding a glycoprotein in the extracellular matrix was significantly associated with frailty in a multivariable model (p = 0.0006). The perception of health-related QoL and subclinical depression contribute to frailty. Their assessment could improve the identification of older patients at increased risk of adverse outcomes.